2020
DOI: 10.1021/acssuschemeng.0c04616
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Solid–Liquid Biphasic Solvent for CO2 Capture: Crystalline Powder Product and Low Heat Duty

Abstract: A nonaqueous, phase-change absorbent of 2-amino-2methyl-1-propanol (AMP)/piperazine (PZ) and environmentally friendly solvent dipropylene glycol dimethyl ether (DME) fixes a number of issues suffered by a solid−liquid biphasic solvent, such as high viscosity of the saturated solution and difficult separation and regeneration of the viscous solid. The solid phase occupies 43% of the total volume while attributes about 94% of the total loading (0.87 mol mol −1 ) of the solution. Beside the formation of AMP-carba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 62 publications
(103 reference statements)
0
12
0
Order By: Relevance
“…65,107,[120][121][122][123] To resolve these limitations, researchers have ventured into synthesizing novel absorbents via hybrid mixing and incorporating promoters or enhancers into CO 2 capture systems. 32,38,65,66,83,118,[124][125][126] The purpose of these initiatives is to combine the advantages of the different absorbents to enhance their CO 2 capture performance and overcome their limitations. 89,127 As numerous hybrid absorbents are being proposed over the years, this subsection only highlights some of the recent development of different hybrid absorbents.…”
Section: Hybrid/novel Absorbentmentioning
confidence: 99%
See 3 more Smart Citations
“…65,107,[120][121][122][123] To resolve these limitations, researchers have ventured into synthesizing novel absorbents via hybrid mixing and incorporating promoters or enhancers into CO 2 capture systems. 32,38,65,66,83,118,[124][125][126] The purpose of these initiatives is to combine the advantages of the different absorbents to enhance their CO 2 capture performance and overcome their limitations. 89,127 As numerous hybrid absorbents are being proposed over the years, this subsection only highlights some of the recent development of different hybrid absorbents.…”
Section: Hybrid/novel Absorbentmentioning
confidence: 99%
“…One popular absorbent system developed is the hybrid of alkanolamines and ILs. 125,126,[128][129][130][131] In 2021, Damanafshan et al 129 analyzed the carbon capture performance of an aqueous MDEA and [Omin][BF 4 ] IL blend. It was reported that the blended absorbent can enhance CO 2 absorption capacity of approximately 0.05 to 2 mol CO 2 /mol amine compared to a typical MDEA solution.…”
Section: Hybrid/novel Absorbentmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to solve this problem, nonaqueous solutions, such as AMP + dipropylene glycol dimethyl ether, 2-ethylhexan-1-amine (EHA) + diglyme, EHA + triglyme, and EHA + tetraglyme are developed to improve the CO 2 absorption performance. [18][19][20] The recent research has focused on the usage of nanofluids to improve CO 2 capture performance. [21][22][23][24] In these researches, nanofluids of graphene-oxide/MDEA, SiO 2 / methanol, and dodecane/methanol are used as CO 2 absorbent.…”
Section: Introductionmentioning
confidence: 99%